Peacebuilding Actors in the Levels of Decentralization in Iraq After 2003: A Study of Local Actors - Ayat Ahmed Salman , Prof. Dr. Omar Jumaah Imran (Journal of International Crisis and Risk Communication Research, 2024)
Peacebuilding in nations is achieved through the presence of multiple actors that work towards enforcing the law and focusing on constitutional institutions with the necessary authority and powers. If these elements are absent, peacebuilding or societal peace and national reconciliation are destabilized, leading to potential collapse. These actors have a crucial role in regulating the actions of individuals and groups within the state through the proper and impartial application of the law. When this is done correctly, a sense of equal opportunity and fair access to rights develops, where every citizen observes their peers with fairness. However, if balance is lacking, feelings of frustration and a sense of deprivation arise, which indicates that societal peace is experiencing instability and disturbances, negatively affecting the surrounding environment. Instead of progress, destruction occurs, creating an obstacle to achieving the desired peace. The responsibility for achieving peace lies with the governing authorities in the state, classified as local actors, and with international actors, represented by international organizations that work to spread awareness, education, and cultural practices. These practices emphasize individuals and encourage a culture of tolerance and citizenship. The discussion on local actors in peacebuilding post-2003 will follow.